Benzene Exposure in Workers From a Waste Oil Regeneration Plant During Ordinary Activities by Air and Biological Monitoring - Campo, Laura; Boniardi, Luca; Olgiati, Luca; Polledri, Elisa; Mercadante, Rosa; Fustinoni, Silvia (La Medicina del Lavoro, 2024)
Background: In the regeneration of waste oil, a strategical technological process for the European Union circular economy action plan, exhausted oils are regenerated to produce high performing oil bases. Aim of this work was to assess the exposure to benzene in plant workers during ordinary activities. Methods: 59 workers, potentially exposed to benzene, and 9 administrative workers from an Italian plant were monitored for the whole work shift with personal air samplers; urinary benzene (BEN-U) and S-phenyl mercapturic acid (SPMA) were measured by mass spectrometry methods in end-shift urine samples. Different job tasks were identified among workers. Results:Median (minimum-maximum) airborne exposures to benzene were <0.9 (<0.9-6.3) and <0.9 (<0.9-0.9) µg/m3, BEN-U and SPMA levels were 0.094 (<0.015-3.095) µg/L and 0.15 (<0.10-9.67) µg/g crt and 0.086 (0.034-0.712) µg/L and <0.10 (<0.10-3.19) µg/g creatinine in workers and administrative workers, respectively. No differences were found among job tasks and between workers and administrative workers, while higher levels were found in smokers than in non-smokers. For all job tasks, the exposure to benzene was always below occupational limit values. Conclusions: This study has investigated for the first time the exposure to benzene of workers employed in the re-refining of exhaust oil. The results showed that normal production activities in regenerating used oils do not pose a risk of exposure to benzene in workers.